Mental computation: an overview on this special issue - Carvalho, Renata (2021)
Mental computation involves engaging mental processes to compute an arithmetic result.However, thereare different perspectives on the typeof computation thatcan be done and howit can be done. Concerning the type of computation that can be done, someresearchersargue that mental computation is the process of computing an exact arithmetic result(Reys et al., 1995), while others consider that mental computation canbe performedusingestimation(Heuvel-Panhuizen, 2001),as Andrews and colleagues present in their article. Regadinghowit can be done, some argue that mental computation only uses mental processes without any external support(Reys et al., 1995), while others accept the use of paper-and-pencil as a support of students reasoning(Buys, 2001;Sowder, 1990).Actually, mental computation involves computing with numbers and rather than with digits (Buys, 2001) and it can be performed to reach an exactarithmeticresult,or to estimate a result. Mental processes are the basis of computing mentally, even if paper-and-pencil is used to note some intermediate results. Further discussion needs to go deeper, so that we can understand why computing mentally is important to include in mathematics curriculum,and what it involves.